Ingenious characterization and assessment of lentil germplasm collection to aphid Acyrthosiphon pisum stress unveils distinct responses - Zafeiriou, Ioannis; Ntoanidou, Symela; Baira, Eirini; Kasiotis, Konstantinos M.; Barmpouni, Theodora; Machera, Kyriaki; Mylona, Photini V. (Frontiers in Plant Science, 2022)
Lentil cultivation is often hampered by aphid population outspreads with detrimental impacts to crop development and production, challenging food safety and agriculture sustainability. The pea aphid (Acyrthosiphon pisum) is a significant threat to lentil in the temperate zone rainfed systems. A set of management practices including resilient cultivars and application of insecticides have effectively controlled aphid infestation. However, the plant defense against insect pests is scantily dissected and limited to the individual components including antibiosis, antixenosis and tolerance that constitute a combination of plant responses to aphids. Utilizing a lentil germplasm collection, we assessed the antixenosis and aphid tolerance in association to important morphological parameters. Physiological parameters including RWC measured at 24h and 48h post-aphid infestation revealed genotype-specific responses. The contents of key plant hormones including salicylic acid (SA), jasmonic acid (JA), abscisic acid (ABA) and indoleacetic acid (IAA) implicated in defense signal-transduction pathways were also determined in lentil accessions after aphid herbivory infestation. In parallel, the expression of hallmark defense genes governed by SA- and JA-signaling pathways was assessed at 24h and 48h post aphid herbivory, revealed significant differentiation patterns among accessions. An interplay of hormone crosstalk is unveiled that possibly governs defense responses and aphid resistance. Besides the metabolomic profiling of accessions under aphid herbivory indicated the indispensable role of key secondary metabolites accumulation such as flavonoids, alkaloids, phenolics and fatty acids as a front line of plant defense and a potential integration of hormone signaling pathways in metabolome reprogramming. Overall, the study presents a panorama of distinct lentil responses to aphids and a critical view of the molecular mechanisms implicated in lentil insect defense to further our insight and advance crop protection and breeding approaches in a climate changing environment.